Alterations in neonatal neutrophil function attributable to increased immature forms. (December 2016) - Makoni, Marjorie; Eckert, Jeffrey; Anne Pereira, H.; Nizet, Victor; Lawrence, Shelley M.
Abstract: At birth neonatal neutrophil composition differs from that of adults due to a higher number of circulating immature forms. To date only a single study has evaluated neutrophil performance based on cell maturity. For this study, we examined functional differences in chemotaxis and phagocytosis between neonatal and adult neutrophils based on cell development and labor exposure. Methods: Neutrophils were obtained by venipuncture from adults and cord blood from healthy term neonates delivered vaginally or by cesarean section. Transwells and the chemoattractant fMLP were used to evaluate chemotaxis. Phagocytosis assays were performed using GFP-labeled E.coli (RS218) and whole blood. Neutrophil maturation was measured by an accurate and verified flow cytometry technique using the markers CD45, CD11b, and CD16. QuantiGene Plex and Procarta immunoassays were used to determine cytokine and chemokine gene expression and protein concentration, respectively. Results: Labor exposure did not alter neonatal neutrophil function in this study. Neonatal and adult mature neutrophils performed chemotaxis and phagocytosis equally well, while immature forms showed marked impairments. Neonatal immature granulocytes, though, completed chemotaxis more proficiently than those of adults. Although cytokine and chemokine levels varied between neonatal and adult groups, no differences were detected in neonates based upon labor exposure. Conclusion: Historically documented functional impairments of neonatal neutrophils may be due to the increased number of developmentally immature forms at birth rather than absolute global deficiencies.